Antenatal screening for haemoglobinopathies in primary care: a cohort study and cluster randomised trial to inform a simulation model. The Screening for Haemoglobinopathies in First Trimester (SHIFT) trial - E Dormandy; S Bryan; MC Gulliford; TE Roberts; AE Ades; M Calnan; K Atkin; J Karnon; PM Barton; J Logan; F Kavalier; HJ Harris; et al. (Health Technology Assessment, 2010)
Objectives: To assess the effectiveness, cost-effectiveness, acceptability and feasibility of offering universal antenatal sickle cell and thalassaemia (SCT) screening in primary care when pregnancy is first confirmed and to model the cost-effectiveness of early screening in primary care versus standard care. Design: A population-based cohort study, cluster randomised trial and refinement of a published decision model. Setting: Twenty-five general practices from two UK primary care trusts (PCTs) in two inner city boroughs with a high proportion of residents from minority ethnic groups. Participants: Practices were considered eligible if they agreed to be randomised and they were able to provide anonymous data on all eligible pregnant women. Participants were at least 18 years old and consented to take part in the evaluation. Interventions: Practices were allocated to intervention, using minimisation and stratifying for PCT and number of partners at the practice, as follows: screening in primary care with parallel father testing (test offered to mother and father simultaneously; n = 8 clusters, 1010 participants); screening in primary care with sequential father testing (test offered to father only if mother identified as carrier; n = 9 clusters, 792 participants); and screening in secondary care with sequential father testing (standard care; n = 8 clusters, 619 participants). Main outcome measures: Data on gestational age at pregnancy confirmation and screening date were collected from trial practices for 6 months before randomisation in the cohort phase. The primary outcome measure was timing of SCT screening, measured as the proportion of women screened before 70 days’ (10 weeks’) gestation. Other outcomes included: offer of screening, rates of informed choice and proportion of women who knew the carrier status of their baby’s father by 77 days (11 weeks). Results: For 1441 eligible women in the cohort phase, the median [interquartile range (IQR)] gestational age at pregnancy confirmation was 7.6 weeks (6.0 to10.7 weeks) and 74% presented in primary care before 10 weeks. The median gestational age at screening was 15.3 weeks (IQR 12.6 to 18.0 weeks). Only 4.4% were screened before 10 weeks. The median delay between pregnancy confirmation and screening was 6.9 weeks (4.7 to 9.3 weeks). In the intervention phase, 1708 pregnancies from 25 practices were assessed for the primary outcome measure. Completed questionnaires were obtained from 464 women who met eligibility criteria for the main analysis. The proportion of women screened by 10 weeks (70 days) was 9/441 (2%) in standard care, compared with 161/677 (24%) in primary care with parallel testing, and 167/590 (28%) in primary care with sequential testing. The proportion of women offered screening by 10 weeks (70 days) was 3/90 (3%) in standard care (note offer of test ascertained for questionnaire respondents only), compared with 321/677 (47%) in primary care with parallel testing, and 281/590 (48%) in primary care with sequential testing. The proportion of women screened by 26 weeks (182 days) was similar across the three groups: 324/441 (73%) in standard care, 571/677 (84%, 0.09) in primary care with parallel testing, and 481/590 (82%, 0.148) in primary care with sequential testing. The screening uptake of fathers was 51/677 (8%) in primary care with parallel testing, and 16/590 (3%) in primary care with sequential testing, and 13/441 (3%) in standard care. The predicted average total cost per pregnancy of offering antenatal SCT screening was estimated to be £13 in standard care, £18.50 in primary care with parallel testing, and £16.40 in primary care with sequential testing. The incremental cost-effectiveness ratio (ICER) was £23 in primary care with parallel testing and £12 in primary care with sequential testing when compared with standard care. Women offered testing in primary care were as likely to make an informed choice as those offered screening by midwives later in pregnancy, but less than one-third of women overall made an informed choice about screening. Conclusions: Offering antenatal SCT screening as part of pregnancy-confirmation consultations significantly increased the proportion of women screened before 10 weeks (70 days), from 2% in standard care to between 16% and 27% in primary care, but additional resources may be required to implement this. There was no evidence to support offering fathers screening at the same time as women. Trial registration: Current Controlled Trials ISRCTN00677850. Funding: The National Institute for Health Research Health Technology Assessment programme.